A Review of Document Image Binarization Techniques - Singh, Pritpal; Singh, Balwinder (International Journal of Computer Sciences and Engineering, 2019)
Binarization is very important pre-processing technique for document images which is used to segment the image into foreground and background pixels. Binarization of degraded documents is very challenging due to uneven background, noise, ink dots, degradation of paper ink due to aging etc. Although many binarization techniques are available, but these standard algorithms are sensitive to noise and do not produce good results on different kinds of degradations. The selection of binarization method for a particular degradation is a very tedious job. In this paper, a survey of recent ongoing research efforts in field of image binarization has been carried out. The purpose of this study is to find the research gap in the field of document image binarization.